Factors influencing student interest in STEM careers: motivational, cognitive, and socioeconomic status - Ijtihadi Kamilia Amalina; Tibor Vidákovich; Könül Karimova (Humanities & Social Sciences Communications)
Abstract There is a disparity between the number of graduates and the demand for professionals in science, technology, engineering, and mathematics (STEM)-related fields globally. This gap underscores the importance of understanding and addressing the factors that drive student interest in the STEM career. Consequently, the education sector around the world is increasingly focused on identifying and improving these influencing factors to better align educational outcomes with the needs of the STEM industry. Thus, this study examined the cognitive (mathematics knowledge, science knowledge, and academic achievement), motivational (self-efficacy and outcome expectation), and socioeconomic status (parents’ education and family income) factors involved in predicting student interest in pursuing STEM careers. The data were conducted from tests, questionnaires, and documents from grade 10 and 11 students (n = 738) in Indonesia. In addition, two theoretical models (i.e., Models 1 and 2) were developed and were tested using structural equation modeling. The results showed that both models met the required standards for good fit, but Model 2 fit the data better overall, while Model 1 was only slightly below the ideal range for one measure (RMSEA). We found that motivational and cognitive factors were crucial predictors in shaping student interest in general STEM and STEM discipline–specific fields. A strong indirect effect was found in the relationship between self-efficacy and career interest through the outcome expectation factor, and the indirect effect of mathematics and science knowledge on interest in STEM careers through academic achievement is an important concern. Similar and different factors are discussed in terms of student interest in general STEM-related fields and STEM discipline–specific careers.